AFSPA’s Role in Conflict Zones: A Legal Perspective - Desai, Twinkle Hemant (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Armed Forces (Special Powers) Act, 1958 (AFSPA) remains one of the most contested legislative instruments within India’s constitutional framework. Enacted as an exceptional measure to address internal security challenges in conflict-affected regions, the Act confers extensive operational powers upon the armed forces in areas notified as “disturbed.” While its stated purpose is the maintenance of public order and territorial integrity, the prolonged enforcement of AFSPA has generated sustained concern regarding its implications for constitutional rights, accountability, and democratic governance. This paper examines AFSPA from a legal and constitutional perspective by analysing its legislative evolution, statutory framework, and judicial interpretation. It engages with key judicial pronouncements, including Naga People’s Movement of Human Rights v. Union of India and Extra Judicial Execution Victim Families Association v. Union of India, as well as the findings of expert committees that have reviewed the Act’s operation. The study contends that although national security constitutes a legitimate state objective, the continued operation of AFSPA without effective safeguards risks undermining fundamental rights and the rule of law. It concludes by advocating context-specific reforms aimed at reconciling security imperatives with constitutional accountability and human rights protection.